Digital Worksheets Based on an Open-Ended Approach to Enhance Problem-Solving Skills in 4–5-Year-Old Children - Wika Widiana; Fadlullah; Luluk Asmawati (Universitas Pendidikan Ganesha, 2025)
Problem-solving skills are an important foundation for early childhood cognitive development, but closed learning practices that rely on conventional media do not fully stimulate children's flexible and creative thinking. This study aims to analyze and develop an open-ended digital worksheet and test its feasibility and effectiveness in strengthening early childhood problem-solving skills. The study employed a research and development approach, involving children aged four to five years as test subjects. Data collection was conducted through interviews, observations, and questionnaires, using instruments such as interview guides, problem-solving ability observation sheets, and questionnaires validated by subject matter and media experts. Data were analyzed qualitatively to explain the interview findings and descriptively quantitatively to explain the results of observations and expert validation. The results indicate that the developed product meets the criteria for content and media suitability and effectively stimulates children to develop various problem-solving strategies. The study's conclusions confirm that open-ended digital worksheets contribute to creating more exploratory and meaningful learning. Therefore, educators need to integrate pedagogically designed digital interactive media to support the development of higher-order thinking skills from an early age.